ANALISIS PENDAPATAN PETERNAKAN ITIK PETELUR DI KECAMATAN ALUH-ALUH KABUPATEN BANJAR - Ramdani, M. Luthfi; Herliani, Herliani; Habibah, Habibah (www.ulm.ac.id, 2024)
This research aims to find out how much income the egg-laying duck farming business makesin Aluh-Aluh District, Banjar Regency and evaluate the amount of fixed costs, variable costs,revenue costs, profits and break even points of the laying duck farming business in Aluh-AluhDistrict. This research be carried out in Aluh-Aluh District in Banjar Regency, SouthKalimantan. This research be carried out from March to December 2023 includingpreparation, carrying out surveys or data collection, as well as the process of making reports.The research method used in this research is the survey method, where the data taken is in theform of primary and secondary data. The results of this research show that the average incomeof broiler duck breeders in Aluh-Aluh District, Banjar Regency is different for each scale ofbusiness owned. The largest income was Rp. 597,137,816, with a business scale of 1000heads and the smallest is Rp. 206,704,600 with a business scale of 500 people. With abusiness scale of 1000 heads the income obtained is much grat than with a business scale of500 heads. A large business scale does not guarantee that the income earned will also be large,it all depends on the management carried out by egg-laying duck breeders in Aluh-AluhDistrict, Banjar Regency. The laying duck farming business in Aluh-Aluh District, Banjar Regency with a business scale of 500-1000 birds can be said to be profitable and efficientbecause it has a profit value of R/C>1, namely with an average of 1.5 and a Break Even Point(BEP) value that is The highest is on a scale of 1000 ducks with a total of 263,678 eggs andthe lowest Break Even Point (BEP) is on a scale of 500 ducks with a total of 135,402 eggs.